Research Source Base of the Problem of Reflexion of Personality Gender Peculiarities in the Textbooks of Mathematical Disciplines (End of the ХХ – Beginning of the ХХІ Century) - Hensitska-Antoniuk, Natalia (Pedagogical Discourse, 2013)
The research source base of the Problem of Reflexion of Personality Gender Peculiarities in the Textbooks of Mathematical Disciplines (End of the ХХ – Beginning of the ХХІ Century) has been analyzed in the article. The main groups of the research source base of the indicated problem which is the basis for writing historic-pedagogical dissertation have been singled out. Paying attention to the great number of studied sources, one of the singled groups has been characterized, that includes interpretative sources, namely: monographs, brochures, articles, devoted to the explored topic or which are tangential to it. The submitted sources are divided into such sub-groups: the works of foreign researchers on the problem of gender, the works examining philosophic and theoretical principles of culture and education and their impact on the gender component of education and training, works on the gender psychology and works on pedagogics.